CONDUCTING FEEDBACK ON EXERCISES AND TASKS AT FOREIGN LANGUAGE CLASSES - Лілія Штохман (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
The article deals with a feedback concept as a part of control in educational process. Highlighted are the functions, principles and forms of control in teaching, foreign language in particular. Analyzed are the prerequisites of efficient educational process management and enumerated are some disadvantages of traditional kinds of feedback, according to the investigations of British trainers. In this context, a range of techniques employed by the teacher to facilitate responses from the students to an exercise or task during a foreigh language class described by foreign training coordinators is presented. These are role exchange, interactive, peer checking etc. Some advantages of such kinds of checking are shown and justified. It is revealed that encouraging students to participate, take responsibility and cooperate allows to facilitate and diversify traditional feedback process.